Efectos de la educación superior en el crecimiento económico departamental en Colombia (2016)
This paper aims to explain the effects that have college education on economic growth in the country’s departments. For this becomes a theoretical review of the relationship between economic growth and the education as a source of human capital formation. This is to explain the dynamics of regional development from a perspective of regional disparities. Also, it is estimated an econometric model with data panel using fixed effects. The results suggest that the formation of researchers, who drive the processes of innovation and technical change, has a high degree of explanation on economic growth in the country’s departments, which leads to understanding that higher education impacts in the training of researchers and, thus, on economic growth.